The Toxic Truth About Carbon Nanotubes in Water Purification: a Perspective View - Das, Rasel; Leo, Bey Fen; Murphy, Finbarr (SpringerOpen, 2018)
Without nanosafety guidelines, the long-term sustainability of carbon nanotubes (CNTs) for water purifications is questionable. Current risk measurements of CNTs are overshadowed by uncertainties. New risks associated with CNTs are evolving through different waste water purification routes, and there are knowledge gaps in the risk assessment of CNTs based on their physical properties. Although scientific efforts to design risk estimates are evolving, there remains a paucity of knowledge on the unknown health risks of CNTs. The absence of universal CNT safety guidelines is a specific hindrance. In this paper, we close these gaps and suggested several new risk analysis roots and framework extrapolations from CNT-based water purification technologies. We propose a CNT safety clock that will help assess risk appraisal and management. We suggest that this could form the basis of an acceptable CNT safety guideline. We pay particular emphasis on measuring risks based on CNT physico-chemical properties such as diameter, length, aspect ratio, type, charge, hydrophobicity, functionalities and so on which determine CNT behaviour in waste water treatment plants and subsequent release into the environment.